Age of Onset, Nutritional Determinants, and Seasonal Variations in Menarche in Rural Bangladesh (Journal of Health, Population and Nutrition, 2010)
Menarche is an important milestone in the development of female adolescents. The study assessed the age at menarche using recall, its seasonality, and association with marital and nutritional status (using midupper arm circumference [MUAC]) among 3,923 female adolescents aged 12-19 years in a rural area of Bangladesh. At the time of assessment, most (88%) adolescents had attained menarche at the mean (standard deviation [SD]) age of 12.8 (1.4) years. Age of onset of menarche among married adolescents (13%) occurred earlier than in those who were unmarried (12.6±1.3 years vs 12.9±1.4 years, p